2016
DOI: 10.1038/ncomms10401
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and dynamics of the ligand shell of a water-soluble Au102 nanoparticle

Abstract: Inorganic nanoparticles, stabilized by a passivating layer of organic molecules, form a versatile class of nanostructured materials with potential applications in material chemistry, nanoscale physics, nanomedicine and structural biology. While the structure of the nanoparticle core is often known to atomic precision, gaining precise structural and dynamical information on the organic layer poses a major challenge. Here we report a full assignment of 1H and 13C NMR shifts to all ligands of a water-soluble, ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 28 publications
(39 reference statements)
2
126
1
Order By: Relevance
“…In recent studies the NMR spectra for the ligand layer of Au 102 ‐ p MBA 44 has been fully assigned in water using 2D NMR measurements. This study in combination with dynamical MD simulations confirmed that the arrangement of the ligand layer in solution state is similar to that of the solid‐state structure …”
Section: Figuresupporting
confidence: 71%
“…In recent studies the NMR spectra for the ligand layer of Au 102 ‐ p MBA 44 has been fully assigned in water using 2D NMR measurements. This study in combination with dynamical MD simulations confirmed that the arrangement of the ligand layer in solution state is similar to that of the solid‐state structure …”
Section: Figuresupporting
confidence: 71%
“…[22] In recent studies the NMR spectra for the ligand layer of Au 102 -pMBA 44 has been fully assigned in water using 2D NMR measurements.T his study in combination with dynamical MD simulations confirmed that the arrangement of the ligand layer in solution state is similar to that of the solid-state structure. [24] We envisaged that Au 102 -pMBA 44 ( Figure 1) with its peripheral carboxylic acid groups of pMBA, allowing hydrogen bonds between nanoclusters,p rovides af easible starting point to investigate colloidal superstructures using atomically precise building blocks.W hent he carboxylic acids are in the acid form (protonated), Au 102 -pMBA 44 is soluble in polar solvents such as methanol and dimethyl sulfoxide and insoluble in water. [25] However,upon deprotonating afraction of carboxylic acids (> 22) into sodium salts using aqueous sodium hydroxide,t he nanoclusters become dispersible in water.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise transition and its effects on the particles' properties (for example, catalysis) still remain unclear. In recent years, significant advances have been achieved in the wet chemical synthesis of atomically precise nanoparticles or nanoclusters89, which has opened up new opportunities for fundamental studies at the unprecedented level of atomic precision.…”
mentioning
confidence: 99%